Analisis Sentimen Masyarakat terhadap Penggunaan Sepeda Listrik pada Anak-Anak di Media Sosial X Menggunakan Metode SVM - Lestari, Rohmah Dewi; Isnain, Auliya Rahman (Building of Informatics, Technology and Science (BITS), 2024)
The use of electric bicycles among children is becoming increasingly popular in Indonesia. While offering practicality and mobility efficiency, their usage raises safety concerns, especially for children on the road. Public opinions on this issue are widely discussed on social media platform X (Twitter), with some supporting their use due to practicality and eco-friendliness, while others advocate stricter regulations to ensure children’s safety. This study analyzes public sentiment toward the use of electric bicycles for children using the Support Vector Machine (SVM) method. Data was collected through a crawling process on social media X using the Tweet Harvest tool, resulting in 3,565 entries. The data underwent preprocessing and translation into English for sentiment analysis using TextBlob. Sentiments were labeled, identifying 1,737 negative sentiments (64.24%) and 967 positive sentiments (35.76%). The dataset was divided into 80% for training and 20% for testing. An SVM model with a linear kernel was applied for classification. Performance evaluation using a confusion matrix showed 0.84 accuracy, precision scores of 0.84 (negative) and 0.85 (positive), recall scores of 0.92 (negative) and 0.71 (positive), and F1-scores of 0.88 (negative) and 0.78 (positive). The findings reveal that public sentiment predominantly reflects concerns about children’s safety risks.